2008
DOI: 10.1016/j.dnarep.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The histone methylase Set2p and the histone deacetylase Rpd3p repress meiotic recombination at the HIS4 meiotic recombination hotspot in Saccharomyces cerevisiae

Abstract: The rate of meiotic recombination in the yeast Saccharomyces cerevisiae varies widely in different regions of the genome with some genes having very high levels of recombination (hotspots). A variety of experiments done in yeast suggest that hotspots are a feature of chromatin structure rather than a feature of primary DNA sequence. We examined the effects of mutating a variety of enzymes that affect chromatin structure on the recombination activity of the well-characterized HIS4 hotspot including the Set2p an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 61 publications
2
41
0
1
Order By: Relevance
“…7D; Table S4). Our findings strongly support the notion that histone acetylation is necessary for meiotic recombination, and they are consistent with analyses of hot spot activity in epigenetic mutant strains of yeasts and plants (21,(85)(86)(87). For example, deletion of the S. pombe HAT gene Gcn5, which directs hyperacetylation of the ade6-M26 hot spot, leads to reductions in DSBs and CO rates at this hot spot (21).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…7D; Table S4). Our findings strongly support the notion that histone acetylation is necessary for meiotic recombination, and they are consistent with analyses of hot spot activity in epigenetic mutant strains of yeasts and plants (21,(85)(86)(87). For example, deletion of the S. pombe HAT gene Gcn5, which directs hyperacetylation of the ade6-M26 hot spot, leads to reductions in DSBs and CO rates at this hot spot (21).…”
Section: Discussionsupporting
confidence: 75%
“…For example, deletion of the S. pombe HAT gene Gcn5, which directs hyperacetylation of the ade6-M26 hot spot, leads to reductions in DSBs and CO rates at this hot spot (21). Conversely, deletion of the S. cerevisiae HDAC gene Rpd3 augments HIS4 hot spot activity (86). However, our HDAC inhibitor studies with the CAST/DBA mouse strain, in which the HS22 hot spot is inactive, have also shown that augmenting histone acetylation (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…The histone methyltransferase Set2 directly binds to elongating polymerase II (23)(24)(25)(26)(27) and co-transcriptionally methylates histone H3K36. H3K36me in turn recruits and activates the Rpd3S histone deacetylases and the Isw1a chromatin remodeler to maintain hypoacetylated coding regions (22,28), which suppress cryptic transcription initiation (29 -31) and recombination (32). H3K36me is also responsible for directing the histone acetyltransferases NuA4 and NuA3b to coding regions to facilitate transcription elongation (33)(34)(35).…”
mentioning
confidence: 99%
“…It is important to note that sir2Δ strains have similar high rDNA recombination levels (Gottlieb and Esposito 1989;Clarke et al 2006); however, the high recombination rate is restricted to specific genomic areas (Su et al 2000;Mieczkowski et al 2007). In the esa1Δ sds3Δ sir2Δ strain, the genomic areas susceptible to recombination may be more dispersed than in sir2Δ cells as Rpd3 has a role in repressing mitotic recombination (Dora et al 1999;Merker et al 2008).Finally, to test if the DNA damage resistance of the esa1Δ sds3Δ sir2Δ strain was due to a pseudodiploid state, we transformed a MATa esa1Δ sds3Δ strain with a plasmidborne MATa locus. Enhanced suppression of the DNAdamage-sensitive phenotype was not observed ( Figure 5D).…”
mentioning
confidence: 99%